Estudio de factibilidad para la creación de una empresa de fabricación y distribución en Beer Trucks de cerveza artesanal con sabor a borojó y mangostino en la ciudad de Bogotá D.C. (2020)
The development of this project was about the creation of a company that manufactures and distributes craft beer in Beer Trucks around Bogota city through the creation of new beer styles made with Borojó and Mangostino which are exotics fruits that can be found in the country. To create a company the researcher needs to do some studies to know if the project will give earnings at the end of the period, the project has seven chapters which are the diagnostic, market, technical, administrative, legal, environment and financial studies, this studies let know if the project will give rentability for the investors. The rentability is measured by some financial indicators such as net present value, internal rate of return and the benefit-cost, at the end of the project the results of these indicators were $121.294.325, 36% and 1,72 respectively. This means that the project is viable and will give rentability.